2013
DOI: 10.18632/oncotarget.1359
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stem cells (ASCs) may favour breast cancer recurrence via HGF/c-Met signaling

Abstract: Adipose tissue is a reservoir of Mesenchymal Stem Cells (Adipose-derived Mesenchymal Stem Cells, ASCs), endowed with regenerative properties. Fat graft was proposed for breast reconstruction in post-surgery cancer patients achieving good aesthetic results and tissues regeneration. However, recent findings highlight a potential tumorigenic role that ASCs may have in cancer recurrence, raising some concerns about their safety in clinical application.To address this issue, we established a model where autologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 58 publications
1
111
0
2
Order By: Relevance
“…Other authors have reported that ASCs may be protective, particularly in suppressing tumor growth and stimulating apoptosis. Most of the articles reviewed consistently pointed out that the role of ASCs in tumor development is complex, and that the tumor microenvironment milieu in which ASCs are present and the mechanisms by which they migrate may influence their role in cancer development (41)(42)(43)(44)(45).…”
Section: Complex Nature Of Ascs In Tumor Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have reported that ASCs may be protective, particularly in suppressing tumor growth and stimulating apoptosis. Most of the articles reviewed consistently pointed out that the role of ASCs in tumor development is complex, and that the tumor microenvironment milieu in which ASCs are present and the mechanisms by which they migrate may influence their role in cancer development (41)(42)(43)(44)(45).…”
Section: Complex Nature Of Ascs In Tumor Behaviormentioning
confidence: 99%
“…Several mechanisms linking ASCs and tumor development/ progression have been described, with many studies highlighting the importance of tumor environment modification by ASCs (41)(42)(43)(44). ASCs may play a role in the creation of an inflammatory tumor microenvironment, which promotes tumorigenic activity.…”
Section: Ascs Influence the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when ASCs were co-injected with tumor cells, they promoted the tumorigenic growth of H460 human non-small cell lung cancer cells and U87MG malignant glioma cells in nude mice (5). A similar tumorigenic effect was observed in human prostate (6) and breast (7) cancer cells in mice. Furthermore, co-culture of ASCs enhanced the proliferation of human squamous cell carcinoma cells (8) and the migration of breast cancer cells in a xenograft model (9).…”
Section: Introductionmentioning
confidence: 73%
“…These evidences showed communication between T47D and stem cells. Eterno et al indicated that the expression of HGF/c-Met signal may indicate breast cancer recurrence [28] . The study found that fat stem cells did not directly induce normal breast cells to become cancer cells but instead provided appropriate inflammatory microenvironment for the growth and vascularization of cancer cells by increasing the occurrence of tumorigenic behavior of breast cells.…”
Section: Laboratory Studies Of Adsc and Breast Cancermentioning
confidence: 99%